Recognizing Women’s Agency: Historical Representations of Zubaidah bint Ja’far’s Philanthropy and Patronage in the Abbasid Public Sphere - Siti Mariam Ulfah; Juliani Syafitri; Muhammad Hafis (An-Nida')
This article aims to highlight the strategic role of Zubaidah bint Ja’far, the wife of Caliph Harun al-Rashid, in shaping the intellectual and cultural climate during the Abbasid Dynasty, particularly through women’s agency in informal power structures within the realms of philanthropy and patronage. This study employs a historical-analytical approach by examining primary sources, including classical Islamic historical chronicles, as well as secondary sources that discuss patronage, philanthropy, and the role of women in Islamic history. The analysis is grounded in existentialist gender theory, drawing from Simone de Beauvoir’s “The Second Sex”. Zubaidah succeeded in transcending her social position as “the other” by establishing a tangible influence through social, cultural, and religious initiatives, which included supporting artists, poets, and scholars through literary assemblies at the palace. Her philanthropic activities, such as the construction of the Darb Zubaidah pilgrimage route—now recognized by UNESCO—and large-scale water infrastructure projects, demonstrate her ability to impact public welfare beyond the domestic sphere. These findings indicate that, despite lacking a formal position of power, Zubaidah was able to shape the social and cultural landscape of her time. This study underscores the importance of re-examining the role of women in Islamic history from a more critical and egalitarian perspective, while also creating opportunities for further research on women’s agency across historical periods.